Biomimetic metalloporphyrin oxidase modified carbon nanotubes for highly sensitive and stable quantification of anti-oxidants tert-butylhydroquinone in plant oil. (15th September 2022) - Bin, Zou; Feng, Liu; Yan, Yan
Highlights: A novel biomimetic enzyme electrochemical biosensor was constructed. The catalytic activity of metalloporphyrins was innovatively studied and compared. Short MWCNTs were bound to ZnTPP particles through non-covalent modification. The TBHQ detection limit of ZnTPP/MWCNTs/GCE was 0.027 µM. This sensor has storage resistance that traditional enzyme electrodes do not have. Abstract: This study constructed a novel biomimetic enzyme electrochemical biosensor based on tetraphenyl metalloporphyrins functionalized multi-walled carbon nanotubes (MWCNTs). The effect of central metal ions on the catalytic activity of tetraphenyl metalloporphyrin biomimetic enzyme was investigated. It was found that the change of central metal ions had a significant effect on the catalytic performance of metalloporphyrin and Zinc(II) tetraphenylporphyrin (ZnTPP) had the most excellent catalytic property. The electrochemical behaviors of tert-butylhydroquinone (TBHQ) on ZnTPP/MWCNTs modified electrode were investigated. It was found that the redox peak current was increased significantly, which was attributed to the redox peak current to the electrocatalytic activity of ZnTPP and the synergistic effect between ZnTPP and MWCNTs. A strong linear relationship was shown in the concentration range of 0.01 to 1000 μM. This electrochemical sensor also had excellent repeatability, storage, and interference resistance. This work provided a simple and sensitive method for the determination of TBHQ.